(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2025)
This study explores the dynamics of investor behavior in the context of Peer-to-Business (P2B) crowdlending, focusing on how investor experience influences their investment intensity and risk assumption. Utilizing data from the Spanish P2B lending platform MytripleA, the research analyzes the investment patterns of 1340 private investors across 798 loans. The study investigates the relationship between the length of investors’ experience and their propensity to fund a larger number of projects and to undertake higher risk investments. It addresses key hypotheses that posit a positive correlation between investor experience and the decision to increase investment intensity and risk level. The methodology integrates a robust Partial Least Squares (PLS) structural equation modeling to validate the proposed relationships. Results indicate that experienced investors tend to diversify their investment portfolios by engaging in riskier projects, confirming the hypothesized positive relationships. These findings contribute to the understanding of investor behavior in crowdlending, offering insights for platform operators and potential investors regarding investment strategies and risk management. The study also highlights the importance of investor experience in influencing investment decisions, underlining its role in the dynamic and evolving landscape of crowdlending.